Kedudukan Anak Yang Lahir Di Luar Pernikahan Di Tinjau Dari Kompilasi Hukum Islam - Tri Khartika Nurry; Emmi Rahmiwita Nasution; Irda Pratiwi (Universitas Muhammadiyah Sumatera Utara, 2020)
Article 99 in Compilation of Islamic Law which states that: a legitimate child is a child born in or as a result of a legal marriage and the result of fertilization of a legal husband and wife outside the womb and born by the wife, which means that the child is said to be legitimate when born from marriage official one. If it is said